(untitled) (Pulse, 2014)
We report a case of a 54 year old male who presented with abdominal pain and hematemesis. After thorough workup, a laparotomy was done. It revealed an ante grade intussusception in the afferent limb of a gastrojejunostomy, which was done in 1978 presumably for peptic ulcer disease. In an attempt to find if such cases are still reported and under what circumstances, a Pub med search using: (intussusception) and (gastrojejunostomy or gastroentorostomy) was done and 170 publications were retrieved. Relevant articles were studied and discussed in this case report. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20348 Pulse Vol.6 January-December 2013 p.41-43